Тимчасовий пункт ливарного ремесла на Львівщині і деякі питання металообробки в ранньому залізному віці - Ільчишин, В.В.; Ольговський, С.Я. (Сіверщина в історії України, 2021)
У статті розглядається пам’ятка, відкрита львівськими археологами, яка ще раз підтверджує роботу бродячих/мандрівних ливарників у ранньому залізному віці. Це невелика піщана дюна, на якій
було зібрано підйомний матеріал у вигляді відходів ливарного ремесла. Відсутність культурного шару, решток майстерні або окремих
плавильних печей дозволяє тлумачити цю пам’ятку як тимчасовий пункт, на якому короткий проміжок часу діяли бродячі ремісники, можливо обслуговуючи населення навколишніх землеробських
поселень. У сукупності із наведеними даними про випадкові знахідки ливарних форм висловлено припущення про існування постійного
маршруту пересування бродячих ливарників від ремісничих центрів
Подніпров’я до джерел мідної сировини в Карпатах і на Балканах. The article examines a monument discovered by Lviv archaeologists,
which once again confirms the work of wandering / traveling foundries in
the early Iron Age. In contrast to the previous day, the existence of nomadic
fishing was denied at this time, although a number of facts confirm this
practice. The described monument also supports the existence of wandering
foundries in Scythian times. It is a small sand dune on which lifting material
has been collected in the form of foundry waste and artifacts associated
with this production. Of particular note are the bronze rods, which were
probably commodity ingots. The absence of a cultural layer, remnants
of a workshop or separate smelting furnaces allows us to interpret this
monument as a temporary point where wandering artisans operated for
a short period of time, possibly serving the population of the surrounding
agricultural settlements. In conjunction with the data on accidental finds
of foundry molds, it has been suggested that there is a permanent route
for wandering foundries from the craft centers of the Dnieper to sources of
copper in the Carpathians and the Balkans. Commodity ingots show that it
was not just an area of activity of wandering masters, but a trade route that
connected the Dnieper craft centers with the Carpathian copper deposits.